KONDISI HIDRODINAMIKA DAN OCEANOGRAFI TELUK TOMINI PROPINSI SULAWESI TENGAH - Hamad, Harly (MEKTEK, 2008)
This research aims to predict wave length, velocity, energy and fluks energy of wave, longshore current,tidal wave at shoreline beach of gulf tomini. The wave caused by wind can be predicting by wilson formula.Orientation of wave from north (58%) and from NW (47%) caused by the wind that happen in august todecember with velocity 9,3 – 10,9 m/s. Another parameters of wave i.e : High wave ranging from 1,59 m to2,02 m, wave length between 42 m and 51 m, their period is 5,17 S – 5,71 S. Longshore current = 0,074 m/swith 1,7259 m high of wave at breaker zone in 2,213 m deep. This value contribute to ratio (h/H) is 1,282.According velocity wave give fluks energy 3773 to 6038 Joule/m2. Influks sediment in beach 3,04 to 6,43m3/hour.